Native Religious Traditions - Prithipaul, K. Dad, 1927-; Waugh, Earle H., 1936- (Book collections on Project MUSE., 1979)
Proceedings of the Joint International Symposium of Elders and Scholars, Edmonton, Alberta, September 15-17, 1977.